METHODS OF QUESTIONING IN ARABIC AND YORUBA: A COMPARATIVE STUDY/ Ø£Ø³Ø§Ù„ÙŠØ¨ Ø§Ù„Ø§Ø³ØªÙÙ‡Ø§Ù… ÙÙŠ Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙˆÙŠÙˆØ±Ø¨Ø§: Ø¯Ø±Ø§Ø³Ø© ØªÙ‚Ø§Ø¨Ù„ÙŠØ© - Adebisi, Aliy Abdulwahid; Akanni, Abdullahi Shittu (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
InterrogativeÂ methods is a fundamental part of a language that is common in all human conversation and speeches in their corporate lives, comparative analysis between languages of the same origin and those of different sources have been carried out to fully identify the likely challenges that might be encountered by learners of linguistics and probable lasting solution to those problems, thus, the research aims to study theÂ contrasting between the two languages with specific attempts at reviewing the interrogational methods and in a bid to draw on the differences. The methodology adopted is an analytical and contrastive method, and the major findings of the thesis include: (1) the interrogative methods in both languages are similar, and as such, the student will not encounter many challenges in the course of learning both languages. (2) There are significant differences in the use of the interrogational particles and adaptations in the studied languages. For instance, all of the interrogative elements of Arabic language are generally placed at the beginning of sentences while in the Yoruba language, it varies between the beginning and terminal positions; and (3) Arabic language possess the quality of being composed of the variable and fixed elements but the Yoruba language is mainly composed of fixed elements, and this can pose a big challenge to students.The study concluded that there are no such gaps in interrogative methods of both languages, except in some cases of fixed and non-fixed elements in Arabic, the study therefore, recommended that curriculum designers should consider areas of similarities and dissimilarities while designing curriculum in order to have suitable curriculum for students of Arabic among the YorubaÂ andÂ theÂ necessity that teachers should familiarize themselves with linguistic contrasts; which would enable them to perform their professional assignment and task in the easiest and most efficient.